Introducing the Pseudepigrapha of Second Temple Judaism : Message, Context, and Significance - Gurtner, Daniel M. (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2020)
This book introduces readers to a much-neglected and misunderstood assortment of Jewish writings from around the time of the New Testament. Dispelling mistaken notions of "falsely attributed writings" that are commonly inferred from the designation "pseudepigrapha," Daniel Gurtner demonstrates the rich indebtedness these works exhibit to the traditions and scriptures of Israel's past. In surveying many of the most important works, Introducing the Pseudepigrapha of Second Temple Judaism shows how the pseudepigrapha are best appreciated in their own varied contexts rather than as mere "background" to early Christianity or emerging rabbinic Judaism.
Apocalypses: 1 Enoch -- 4 Ezra -- 2 Baruch -- Apocalypse of Abraham -- Sybilline oracles 3-5, 11 -- Additional writings: 2 Enoch, 3 Baruch, Apocalypse of Zephaniah, Testament of Abraham, and apocalyptic material in the Dead Sea scrolls -- Testaments and related texts: Testament of Moses -- Testament of Job -- Aramaic Levi document -- Testament of Qahat -- Visions of Amram -- Additional writings: Testament of Solomon, Testaments of the twelve patriarchs, Testament of Naphtali (4Q215), and other testamentary material in the Dead Sea scrolls -- Legends and expansions of biblical traditions: Jubilees -- Biblical antiquities -- Genesis apocryphon -- Letter of Aristeas -- Joseph and Aseneth -- Additional writings: Life of Adam and Eve (Greek), 4 Baruch, and Ezekiel the tragedian -- Psalms, wisdom literature, and prayers: Psalms 151-155 -- Psalms of Solomon -- Sentences of Pseudo-Phocylides -- Additional writings: Hellenistic synagogal prayers, Prayer of Joseph, and Prayer of Nabonidus (4Q242)
Includes bibliographical references (pages 384-417) and indexes.
Keywords: Apocryphal books (Old Testament) -- Criticism, interpretation, etc; Judaism -- History -- To 70 A.D.; History; Criticism, interpretation, etc